The Pentateuch: international perspectives on current research - Dozeman, Thomas B.; Schmid, Konrad; Shṿarts, Barukh Yaʿaḳov (Forschungen zum Alten Testament, 2011)
The Pentateuch is both the literary capstone and the central core of the Hebrew biblical canon. It contains many of the best known and most influential literary texts of world literature. A firm conclusion of biblical research is that the sweeping narrative of the Pentateuch that begins with creation and concludes with the death of Moses was not composed by one author, but is the result of a literary process that took place over hundreds of years. Yet there remains significant debate among international researchers on the composition of the Pentateuch. The present volume contains a collection of articles from an international conference in Zürich that brought together leading voices from North America, Europe, and Israel to evaluate the present state of research on the composition of the Pentateuch. The aim of the conference was to clarify differences in methodology and to identify points of convergence in the present state of pentateuchal research as a basis for further discussion. With contributions by:Reinhard Achenbach, Rainer Albertz, Graeme Auld, Joel S. Baden, Michaela Bauks, Erhard Blum, David M. Carr, Thomas B. Dozeman, Jan Christian Gertz, Itamar Kislev, Israel Knohl, Gary N. Knoppers, Reinhard G. Kratz, Thomas Krüger, Christoph Levin, Christophe Nihan, Saul M. Olyan, Thomas Römer, Konrad Schmid, Baruch J. Schwartz, Sarah Shectman, Jean-Louis Ska, Benjamin D. Sommer, Jeffrey Stackert, Christoph Uehlinger, James W. Watts
Keywords: Bible -- Pentateuch -- Criticism, interpretation, etc -- Congresses; Bible. Pentateuch; Konferenzschrift -- 2010 -- Zürich; Aufsatzsammlung; Intertextualität; Bibel; Komposition; Bibel / Altes Testament; Literarkritik; Forschung; Exegese